EVALUATION OF COTTON MUTANTS FOR WATER DEFICIT CONDITION - MUNIR, MA; BASHIR, H; ZAGHUM, MJ; AZIZ, S; AKHTAR, S; AHMAD, NH; KANWAL, S; KIRAN, S; TIPU, ALK; LIAQAT, S; et al. (Biological and Clinical Sciences Research Journal, 2022)
Cotton (Gossypium hirsutum ssp.) belongs to the genus Gossypium from the family Malvaceae. About 100 genera are in the family Malvaceae and about 1500 species. It is grown worldwide for oil, seed, and fiber. A major problem in cotton cultivation is a drought that’s why this experiment was planned to evaluate the cotton mutants for drought tolerance. A variety of cotton Cyto-155 was mutated with gamma rays at different intensities such that 20kR, 25kR, 30kR, and 35kR, to obtain some genetic variation. Mutated seed along with non-mutated of that cotton variety was sown in split plot layout under randomized complete block design with three replications, under the normal irrigated condition with six irrigations and water stress condition with two irrigations at maturity data was collected for plant height, number of monopodial branches, number of sympodial branches, bolls per plant, boll weight, seed index, GOT%, lint index, seed cotton yield, relative water content and excised leaf water loss.Results showed a highly significant effect of genotype and water regime on all observed traits. Water regime × genotype interaction was also highly significant for plant height, number of sympodial branches, seed index, boll weight, lint index, and excised leaf water loss. Water regime × genotype interaction was non-significant for number of monopodial branches, bolls per plant, GOT%, seed cotton yield, and relative water content. Mean comparison indicated that seed mutated at 30kR and 35kR performed well for all yield-related traits in both irrigated conditions.